PENGARUH GERAKAN ETNONASIONALISME IDENTITARIAN KULIT PUTIH TERHADAP GELOMBANG TERORISME (STUDI KASUS: PENEMBAKAN MESJID ALNOOR DAN LINWOOD ISLAMIC CENTER DI SELANDIA BARU TAHUN 2019) - Dwida, Catherine Saulina; Saeri, Mhd. (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research discusses the impact of the white ethnonationalism movement from Identitarian group on the wave of terrorism. White ethnonationalist terrorism has influenced the number of terror attacks in the past 20 years. This research uses a constructivist and theoretical perspective Fourth Waves Terrorism. Constructivists view personal identity as a unique personality that differentiates them from other individuals. The identity of this category is relatively stable because the attributes it possesses are inherent from the start, such as ethnic, religious, cultural identity, and so on. Then the ethnonationalism movement emerges because of the identity itself, thus encouraging actors who have this personal identity to defend their own identity, even through violent means such as terrorism. This research shows the influence of the Identitarian white ethnonationalist movement as a new wave of terrorism seen by the massive attack by white ethnonationalist extremists that occurred in the city of Christchurch, New Zealand by Tarrant Brenton. DWithin 36 minutes on 15 March 2019, Brenton Tarrant, an Australian right-wing extremist shot dead 51 people at two mosques in Christchurch in the deadliest terrorist attack in New Zealand history. This attack inspired further attacks from the Identitarian group or from other white ethnonationalist extremist groups. Keywords: Four Waves of Modern Terrorism, White Ethnonationalists, Christchurch Shooting